DESA WISATA SEBAGAI COMMUNITY BASED TOURISM - Dhimas Setyo Nugroho (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
Abstract The concept of community-based tourism in the dome house tourism village has succeeded in becoming a tool to trigger the development of the dome house resident and its environment. All of the development can be obviously seen from the economic, social, cultural, environmental and political aspects with a very enthusiastic participation of the resident. The rapid development of the resident and their high participation can emerge a strategy to make the tourist village survive from the tourism industry competition. In this case, the author found that there is a connection between the high level of community participation and the rapid development as the result of it.Â  Therefore, the more the resident willing to participate, the more it will affect the development of the resident and its environment. This research uses qualitative method. The data were obtained by conducting interview, observation, and documentation. After those steps, the data were processed by interactive and SWOT analysis. Then, questionnaire was used to validate the data towards 21 residents.Â Keyword: Community Based tourism, Ladder of participation